Pengaruh Zikir Lazimah terhadap Ketenangan Jiwa Para Santri yang Terkena Stress - Aab Abdilah Mursyid; Cucu Setiawan; Muhtar Solihin (Jurnal Riset Agama, 2022)
Mental is something that is very vital in living life. If a person's mental health is healthy, daily activities will run smoothly and live a happy life which can be transmitted to family, relatives and the environment. But there are still many people who are mentally disturbed so that they live a life full of anxiety. Not for the santri who are in all the pesantren, many of them are mentally disturbed. The contributing factors, among others, are demanding knowledge and unrealized desires resulting in stress and anxiety. This study aims to determine the effect of dhikr Lazimah on mental health which is carried out at the Al-Falah Biru Islamic boarding school, the Tijaniyah tarekat and to find out the Tijaniyah dhikr Lazimah method which is carried out at the Al-Falah Biru Islamic boarding school. The research method used in this study is a quantitative method. The results of the study show that the influence of the usual dhikr affects their mental health, as evidenced by the students who are stressed and then practice the usual dzikr they are free from these psychological diseases. The time of its practice every day is carried out munfarid (individual). In Lazimah remembrance consists of reading istighfar, sholawat and tahlil.